Penerapan Metode Design Thinking dalam Perancangan Aplikasi Layanan Pengaduan Hukum Berbasis Mobile - Shafa, Salsabiyla Alya; Muchayan, Achmad (STMIK Banjarbaru, 2024)
Indonesia is a country based on law, presumably all aspects in the territory of the Republic of Indonesia have been applied fairly and evenly. The number of legal cases is increasing, especially in the city of Surabaya, and the lack of public knowledge about legal complaints so that a legal aid institution is needed that can serve digitalized complaints in order to cover people from all walks of life. Therefore, a mobile-based application design was made to facilitate the process of complaints by the community to legal institutions. The method used in this research is using design thinking and for usability testing using the system usability scale method by distributing questionnaires. The results obtained show that application users feel comfortable from the features that have been developed. This score is included in the